Analisis Gaya Kepemimpinan Kepala Sekolah di Sekolah Dasar Muhammadiyah 1 Margahayu Kab. Bandung - Humaeriyah, Hani; Sofianti, Wanda; Zakaria, Faiz; Yunda, Annisa; Hardian, Salman (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the leadership style of the principal at SD Muhammadiyah 1 Margahayu in managing teachers and implementing managerial functions. This research employed a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The informants consisted of the principal, vice principals, and teachers selected using purposive sampling. Data were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the principal applies a democratic-participative leadership style combined with situational and delegative approaches. Teachers are involved in decision-making, provided with clear and humanistic guidance, and given autonomy in determining teaching methods in accordance with the curriculum. This leadership style enhances teacher involvement, professional performance, and school management effectiveness.